2014
DOI: 10.1002/ejp.587
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic interaction between ondansetron and acetaminophen after tonsillectomy in children: The Paratron randomized, controlled trial

Abstract: An interaction between acetaminophen and ondansetron is suggested, with children receiving three times more morphine during pain titration in the recovery room. More studies are necessary to evaluate whether this finding is clinically relevant enough to preclude the simultaneous perioperative administration of both drugs in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In this study, subjects were in a similar status in terms of demographic variables in order to reduce bias in the results. This finding was in line with the findings of the study by Ramirez et al [6]. Surprisingly, the frequency of nausea in the recovery unit was significantly higher in the intervention group who received ondansetron, an antiemetic drug plus acetaminophen compared to the control group but this difference was not significant in later assessments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, subjects were in a similar status in terms of demographic variables in order to reduce bias in the results. This finding was in line with the findings of the study by Ramirez et al [6]. Surprisingly, the frequency of nausea in the recovery unit was significantly higher in the intervention group who received ondansetron, an antiemetic drug plus acetaminophen compared to the control group but this difference was not significant in later assessments.…”
Section: Discussionsupporting
confidence: 91%
“…Sample size was calculated based on the findings of the study by Ramirez et al [6], which reported the percentage of opioid administration in patients who received acetaminophen and ondansetron as 57.1% and in patients who received acetaminophen alone as 20.6%, considering power = 80% and alpha error = 0:05 using the following inequality equation two sided; the sample size was calculated as 23 patients in each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studying on the involvement of 5-HT3 receptors yielded conflicting results in each animals and humans [38,39,[44][45][46][47][48][49][50].…”
Section: Different Molecular Targets Of Am404mentioning
confidence: 99%
“…However, investigations of the involvement of 5-HT 3 receptors yielded conflicting results in both animals [36,42,43,47,49,50] and humans [51][52][53][54]. Interestingly, some of these studies showed that tropisetron, a nonspecific 5-HT 3 receptor antagonist, blocked the analgesic effect of paracetamol.…”
Section: Involvement Of the Serotonergic Systemmentioning
confidence: 99%